THE INCOME STATEMENT FORMAT NEW TRENDS FROM THE ADOPTION OF INTERNATIONAL FINANCIAL REPORTING STANDARDS (IFRS) AND EXTENSIBLE BUSINESS REPORTING LANGUAGE (XBRL) - Doni, Federica (European Scientific Journal, ESJ, 2013)
The Annual Report is a good mean of describing the situation of a company to all the stakeholders although it is difficult to compare Annual Reports coming from different entities. A process of harmonization of European accounting standards was started in order to bring Annual Reports into line and it is currently being carried out through the adoption of IFRS standards. Once Annual Reports have been created adopting a common accounting standard, the very next step is to code them using the same IT language. If a common computer language is selected, Annual Reports or other documents can easily be compared without recoding and retyping them. The starting point of this process is the definition of an appropriate taxonomy to be used by both those drafting and reading the documents. The process of adopting an appropriate set of accounting standards, selecting the related taxonomy and, finally, drawing up documents using a new business language, called eXtensible Business Reporting Language (XBRL) leads companies to produce sound, meaningful and clear documents that greatly improve sharing of useful information. Moreover, the adoption of IFRS standards and XBRL encoded statements provides a set of measures for building sound and widely accepted models. The aim of the present paper is to analyze the changes to income statement presentation and the new concept of financial performance that emerges as a result of the adoption of IFRS and XBRL language. The drawing up of the Income Statement by XBRL may improve the financial performance measurement and disclosure with many benefits for all the stakeholders.